Reimagining Numeracies: Empowered, Game-Informed Meaning Making in and beyond the Pandemic Era - Abrams, Sandra Schamroth (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2021)
This article focuses on how a game-informed culture in public school math classes sustained interaction, cooperation, and empowered meaning making when COVID-19 mandates closed school buildings and education went fully online. More specifically, the game-informed learning environment supported the students’ development and discussion of their multimodal numeracies, and the highlighted activity reveals how the generation of math memes can foster students’ engagement in creative and empowered practices. Underscored throughout this article is the importance to embrace the expansiveness of numeracies in order to recognize, value, and support students’ meaning making.